Prevention of Unauthorized Access to Electronic Health Records using Docker - Deepa Vishnu, Kodiya; Chitra, K.; Zuriani Hayati, Abdullah (INTI International University, 2024)
This research focuses on securing electronic health records (EHRs) in cloud environments using Docker. The goal is to prevent unauthorized access and data loss while uploading EHRs to the cloud. By leveraging Docker's containerization capabilities, we propose a security framework that includes encryption, access control, and authentication protocols. Through extensive testing, we demonstrate the effectiveness of our approach in enhancing EHR security. This research provides valuable insights for healthcare organizations and cloud service providers seeking to protect sensitive medical data while leveraging the advantages of cloud computing.